The Shepherd's Guide Through the Valley of Debt and Financial Change - Anita Dale (Journal of Financial Therapy, 2012)
"The Shepherd’s Guide Through the Valley of Debt and Financial Change" is intended to guide lay counselors/therapists and other leaders in churches and religious-based organizations through discussions with individuals about a wide variety of financial topics.
Keywords: financial therapy; financial counseling